Development of Autograph-Assisted Teaching Materials to Improve Students' Mathematical Literacy Skills Phase F - Ramlan, Wahyudi; Zetriuslita, Zetriuslita; Suripah, Suripah; Widiati, Indah (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Mathematical literacy is a crucial competency in 21st-century education however, international assessments such as PISA indicate that Indonesian students still have low levels of mathematical literacy. This study aims to develop mathematics teaching materials assisted by Autograph software to enhance the mathematical literacy skills of Phase F students in the topic of geometric transformations.. This research employs the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were students of Class XI-4 at SMA Negeri 4 Tanah Putih. The instruments used included validation sheets, mathematical literacy tests (pretest and posttest), student response questionnaires, and observations. The results of the study show that the developed teaching materials are highly valid, with an average validation score of 89.10%, practical based on student responses with a score of 79.73% categorized as “practical,” and effective based on an N-gain score increase of 0.43 and a statistically significant t-test result. Therefore, the Autograph-assisted teaching materials are considered valid, practical, and reasonably effective in improving students' mathematical literacy skills in geometric transformations.